Past its expiry date? The SILL in modern mixed-methods strategy research - Amerstorfer, Carmen M. (Studies in Second Language Learning and Teaching, 2018)
Has the Strategy Inventory for Language Learning (SILL) passed its expiry date? The SILL (Oxford, 1990) was designed as a self-evaluation tool to measure the frequency of language learning strategies used by foreign and second language (L2) learners. With simple mathematics, learners can analyze their strategy preferences overall and in six categories (i.e., memory, cognitive, compensation, metacognitive, affective, and social strategies). Diverging from its original purpose, the SILL became the most popular instrument in LLS research, which brought widespread acclaim but also criticism. This article explains what makes the SILL an extraordinary tool for learners, teachers, and researchers and how it can be adapted to suit specific contexts and the demands of a modern world. An example of how the SILL can be integrated into mixed-methods research demonstrates how the instrument can fulfil additional purposes to those originally intended. Despite its naturally quantitative orientation, the SILL contributed to the acquisition of rich qualitative information, which enabled a holistic view of five individual L2 learners. In addition to new insights about strategic L2 learning, the study attests that the SILL has not expired yet, but perhaps needs a modern touch, for instance, in the form of adaptation or combination with other research methods and the inclusion of strategies for learning language with technology.